Collaborative innovation and the role of the innovation manager - Perry-Smith, Jill (Henry Stewart Talks, 2022)
Collaborative creativity, Innovation manager, Intraorganizational communication, Informal organization, Idea journey, Risk, Shared vision, Collaborative structure